Disaster awareness and preparedness of micro, small and medium enterprises: The case of Taunggyi (Myanmar) - Zin Mar Than; Tin Tin Kyi; Saw Sandar Oo; San San Htwe; Khin Su Su Wint; Sai Tun Tun; Zin Nwe Myint; Kraas, Frauke (ERDKUNDE, 2026)
Myanmar is a disaster-prone country, experiencing frequent hazards, such as fires, floods, cyclones, landslides, heatwaves and droughts, as well as a high earthquake risk. In such countries, it is crucial that societies become as resilient as possible to disasters. To improve resilience, it is essential that there is a solid understanding of disaster awareness and preparedness throughout society, as this is a prerequisite for successful disaster risk management. In most countries, including Myanmar, micro, small and medium-sized enterprises (MSMEs) form the backbone of the economy and society. These enterprises generate income (by offering jobs) and make a significant contribution to the livelihoods of local people. However, very little is known about the relationship between such enterprises and disasters. The present study focuses on Myanmar and aims to reduce this knowledge gap by answering the following three questions: (1) How do enterprises perceive and assess disasters? (2) How intensively and with which measures do enterprises prepare for such an event? (3) What kind of differences in terms of disaster awareness and preparedness exist in relation to enterprise characteristics (e.g. enterprise size, previous disaster experience). The research is based on a mixed-methods approach. A quantitative survey was conducted with 300 enterprises in Taunggyi, Myanmar, in 2023, and 18 qualitative interviews were conducted with experts working in MSME development and enterprise owners in 2023 and 2024. The results show that awareness and preparedness measures are not satisfactory. While enterprises are well prepared with regard to fire extinguisher maintenance and hygiene measures, deficits exist regarding data security, warning apps and insurance coverage. Enterprises with previous disaster experience have higher awareness levels and have implemented more preparedness measures. Other enterprise characteristics (e.g. firm age and firm size) have a comparatively smaller impact.